Make the rules ebook - Barrows, Annie (Ivy and Bean, 2012)
Bean's older sister, Nancy, is going to Girl Power 4-Ever Camp, where she will do Crafts and Music and First Aid and other secret things that Bean will never know about because girls have to be eleven to go to Girl Power 4-Ever Camp. Bean doesn't care. She doesn't want to go to camp. She wouldn't go even if they begged her. So ha. So ha ha. So—wait a second! Bean and Ivy can make their own camp, their own better camp: Camp Flaming Arrow, where counselors Ivy and Bean will give a whole new meaning to Crafts, Music, First Aid, and hands-on learning! Includes bonus material! - Sneak peek chapter from the next book in the Ivy + Bean series Ivy and Bean Take the Case by Annie Barrows, illustrated by Sophie Blackall - A guide to making your own camp - Other fun games